2003
DOI: 10.2175/106143003x140980
|View full text |Cite
|
Sign up to set email alerts
|

Linking Nitrifying Biofilm Structure and Function through Fluorescent In Situ Hybridization and Evaluation of Nitrification Capacity

Abstract: Fluorescent in situ hybridization (FISH) was used to quantify the ammonia‐oxidizing populations within intact biofilm samples collected from a full‐scale nitrifying trickling filter (NTF). Ammonia, nitrite, and nitrate concentrations were measured for aqueous samples taken in conjunction with biofilm samples at multiple filter depths. The ammonia removal capability of collected biofilms was evaluated by transferring the biofilms to laboratory batch reactors. Nitrate plus nitrite generation rates were calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Many studies have analyzed the microbial community of biofilms using denaturing gradient gel electrophoresis (DGGE) (Boon et al 2002;Lyautey et al 2005) or fluorescence in situ hybridization (FISH) (Schramm et al 1996;Biesterfeld et al 2003). However, DGGE and FISH analysis are not able to determine the specific population composition and their relative abundance within these filters.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have analyzed the microbial community of biofilms using denaturing gradient gel electrophoresis (DGGE) (Boon et al 2002;Lyautey et al 2005) or fluorescence in situ hybridization (FISH) (Schramm et al 1996;Biesterfeld et al 2003). However, DGGE and FISH analysis are not able to determine the specific population composition and their relative abundance within these filters.…”
Section: Discussionmentioning
confidence: 99%
“…This was shown for clusters of ammonia oxidisers that produce nitrite for clusters of nitrite oxidisers. The separate metabolic activities of these 2 groups led to a consumption of ammonia and oxygen near the biofilm surface and the simultaneous production and consumption of nitrite deeper underneath the surface 103,104 .…”
Section: Diffusion and Gradient Formation Of Reactive Species In Biofmentioning
confidence: 99%
“…The degree to which microbial populations specialize in RAS and whether this specialization is indicative of specific environmental factors is not yet fully understood, but some studies have demonstrated an explicit relationship between the presence of distinct microbial populations and environmental conditions in RAS. For example, Based on fluorescence in situ hybridization (FISH) studies, changes in both the abundance of ammonia-oxidizing bacteria and its species composition have been postulated as in situ indicators of the biological impact of ammonia (Okabe et al 1999;Biesterfeld et al 2003). Michaud et al (2014) further revealed a negative relationship between the nitrification efficiency and carbon/ nitrogen (C/N) ratio through the construction of cDNA clone libraries.…”
Section: Introductionmentioning
confidence: 99%